2010
DOI: 10.1136/thx.2009.129668
|View full text |Cite
|
Sign up to set email alerts
|

Variability of lung function predicts loss of asthma control following withdrawal of inhaled corticosteroid treatment

Abstract: Background One aspect of a multidimensional approach to understanding asthma as a complex dynamic disease is to study how lung function varies with time. Variability measures of lung function have been shown to predict response to b 2 -agonist treatment. An investigation was conducted to determine whether mean, coefficient of variation (CV) or autocorrelation, a measure of short-term memory, of peak expiratory flow (PEF) could predict loss of asthma control following withdrawal of regular inhaled corticosteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…In our study, we measured the fluctuation as the absolute variability irrespective of whether the level was higher or lower in any one direction. Frey and colleagues reported that the exponent of long-range fluctuation (a value) of FeNO and PEF predicted individual future risks of asthma exacerbation and reflected the current state of asthma control [6,17,35,40]. Our short-term analysis over only 2 weeks indicated that the diurnal fluctuation in FeNO was more related to asthma control than PEF was.…”
Section: Discussionmentioning
confidence: 76%
“…In our study, we measured the fluctuation as the absolute variability irrespective of whether the level was higher or lower in any one direction. Frey and colleagues reported that the exponent of long-range fluctuation (a value) of FeNO and PEF predicted individual future risks of asthma exacerbation and reflected the current state of asthma control [6,17,35,40]. Our short-term analysis over only 2 weeks indicated that the diurnal fluctuation in FeNO was more related to asthma control than PEF was.…”
Section: Discussionmentioning
confidence: 76%
“…Authors noted that PEF readings are feasible and qualitatively appeared to track disease and symptoms, but symptom-based interventions may be more time and cost-effective. Monitoring changes in PEF as the mean, coefficient of variation, or autocorrelation and its predictive power for loss of asthma control following withdrawal of ICS was studied by Thamrin et al [32 ]. Mild to moderate asthma patients provided PEF data over a 6-week follow-up and found that mean and coefficient of variation of PEF changes were correlated to loss of control.…”
Section: Pulmonary Functionmentioning
confidence: 98%
“…For many years, the diurnal variation in PEF has been recognized to be more severe in patients with greater symptoms of asthma and in those with more difficult to control, or brittle, asthma (56,57). Indeed, monitoring the variability in PEF within the first 2 weeks after withdrawal of inhaled corticosteroids may help predict loss of asthma control (58). Similarly, a drop in PEF combined with increased symptoms during a 1-week period have been shown to define a so-called "action point" beyond which a worsening of asthma will occur within the next 5 days (59).…”
Section: Assessment Of Disease Status and Future Riskmentioning
confidence: 99%
“…We have already seen that fractal-type fluctuations of lung function over time may help to assess disease status and risk (58,60,62,65,72,77,78) and to monitor therapy success (58,60,79). Furthermore, in asthma, fluctuations in inflammatory markers such as fractional exhaled nitric oxide are related to symptoms (62,80), and the degree of concordance between the temporal changes in the biomarker and the temporal changes in daily symptoms may even serve as a measure of disease stability (62).…”
Section: Temporal Phenotyping: Extending Variability Analyses For Botmentioning
confidence: 99%